Mentoring the mentors: a scalable professional development model for graduate teaching assistants and undergraduate learning assistants in large-enrollment CUREs - Kevin Hernández García; Alexander H. Bower; Ana Elisa García-Vedrenne (Journal of Microbiology & Biology Education)
ABSTRACT Course-based undergraduate research experiences (CUREs) incorporate authentic research into undergraduate curricula, offering significant benefits in student retention, graduation rates, and pursuit of science, technology, engineering, and mathematics (STEM) careers. However, graduate teaching assistants (GTAs) and undergraduate learning assistants (ULAs) rarely receive the specific pedagogical training required for CURE instruction. We share an integrated professional development (PD) model for GTAs and ULAs in a large-enrollment CURE that addresses this need. Our model integrates training for both GTAs and ULAs simultaneously into mandatory instructional meetings, providing just-in-time training for upcoming topics and addressing unique CURE facilitation needs. This PD model has been effective in a CURE with a large instructional team and can be scaled up or down as needed. We present results from a post-pre survey asking instructional team members to reflect on their self-efficacy regarding the nine learning outcomes of the implementation. All learning outcomes show an increase in self-efficacy for GTAs and ULAs. By equipping both GTAs and ULAs to navigate the unique challenges of CURE instruction, this PD model may enhance the overall effectiveness of these valuable undergraduate research experiences.